Crack Propagation and Burst Pressure of Pipeline with Restrained and Unrestrained Concentric Dent-Crack Defects Using Extended Finite Element Method - Allan Okodi; Yong Li; Roger Cheng; Muntaseer Kainat; Nader Yoosef-Ghodsi; Samer Adeeb (Applied Sciences, 2020)
Mechanical damage in form of dents, cracks, gouges, and scratches are common in pipelines. Sometimes, these damages form in proximity of each other and act as one defect in the pipe wall. The combined defects have been found to be more injurious than individual defects. One of the combined defects in pipeline comprises of a crack in a dent, also known as dent-crack defect. This paper discusses the development of finite element models using extended finite element criterion (XFEM) in Abaqus to predict burst pressure of specimens of API X70 pipeline with restrained and unrestrained concentric dent-crack defects. The models are calibrated and validated using results of full-scale burst tests. The effects of crack length, crack depth, dent depth, and denting pressure on burst pressure are investigated. The results show that restrained dent-crack defects with shallow cracks (depth less than 50% wall thickness) inside dents do not affect pipeline operations at maximum allowable operating pressure if crack lengths are less than 200 mm. Releasing restrained dent-cracks when the pressure is at maximum allowable operating pressure can cause propagation of deep cracks (depth of 50% wall thickness or more) longer than 60 mm. However, only very long cracks (200 mm and higher) propagate to burst the pipe. Cracks of depth less than 20% of wall thickness inside dents formed at zero pressure are not propagated by the maximum allowable operating pressure. Dent-crack defects having dents of depth less than 2% outside diameter of pipe behave as plain cracks if the dents are formed at zero denting pressure but are more injurious than plain cracks if the dents are formed in pressurized pipes.